البطالة الإجبارية في محافظة بغداد "مدينة الصدر": دراسة في جغرافيا السكان - العبادي، إنعام سمير محي (الجامعة المستنصرية - مركز المستنصرية للدراسات العربية والدولية, 2023)
إن مدينة (الصدر) في بغداد تعد من أكثر المناطق ازدحاما من حيث عدد السكان فضلًا عن أعداد الشباب الخريجين والمؤهلين بشكل كبير للعمل، ولكن لأسباب كثيرة سياسية واقتصادية وأمنية لم يستطع غالبية شباب المدينة من الحصول على عمل دائم سواء في القطاع العام أو الخاص، وفي بحثنا الحالي سنناقش مسألة البطالة الإجبارية التي يعاني منها شباب هذه المدينة أملا في الخروج بمقترحات تعالج هذه الظاهرة. يسعى البحث الحالي إلى التعرف على ظاهرة البطالة الإجبارية لدى عينة من الشباب العاطلين عن العمل في مدينة بغداد (مدينة الصدر) ومن أجل تحقيق أهداف البحث الحالي فقد اتبعت الدراسة المنهج الوصفي المسحي من خلال عينة من العاطلين عن العمل من فئة الشباب بلغت (150) في ضوء مجموعة من المتغيرات الديمغرافية، ومن أجل جمع البيانات والمعلومات اللازمة، فقد أدت الدراسة استبيان لقياس متغير البحث، واستخرج له مجموعة من الخصائص الإحصائية المناسبة من صدق وثبات وقد تم تطبيق الأداة على العينة وتوصلت الدراسة إلى النتائج التالية: 1. تراكم الخريجين سواء على مستوى الكليات الحكومية أم الأهلية ساهم في وصول فائض الخريجين إلى مستوى أعلى من نسبة احتياج سوق العمل إليهم مما فرض البطالة الإجبارية على فئة الشباب. 2. إن البطالة الإجبارية تعود إلى سوء تخطيط، وعمل الجهات المختصة التي تخطط للموارد البشرية في الجامعات، وسوق العمل المطلوب مما انعكس بشكل سلبي على واقع خريجي الجامعات المؤهلين للعمل. 3. إن استراتيجية الدولة في توظيف الخريجين دون الالتفات إلى القطاع الخاص أمر غير سليم وساهم في تفاقم الحالة. 4. إن انتظار الخريج دون السعي للحصول على عمل في القطاع الخاص أو حتى على مستوى المشروعات الصغيرة ساهم في تفاقم هذه الأزمة لدى الشباب. 5. إن إقبال الطلبة على تخصصات معينة من أجل الحصول على وظيفة في المستقبل ساهم بشكل سلبي في رفع معدلات البطالة. 6. إن لجوء الدولة إلى التعليم التقليدي، دون وجود تطورات حديثة في أساليب ومناهج وطرق التدريس أدى إلى مخرجات تربوية لا تمتلك مهارات العمل الواقعي وبالتالي انعكس على إمكانية توظيفهم في العمل بشكل سلبي. 7. إن الفساد السياسي بعد عام 2003 ساهم بشكل سلبي في التأثير على قدرة الدولة في استيعاب الشباب والخريجين في مفاصل الدولة أو في القطاع الخاص. 8. إن للتعليم الجامعي الأهلي بعد 2003 أثر سلبي في رفع حجم ظاهرة البطالة الإجبارية من خلال طبيعة المخرجات والعدد المتخرج. 9. إن قيام جهات التخطيط في الدولة بالربط بين عدد الخريجين المطلوبين بشكل حقيقي لسوق العمل أمر مهم في القضاء على هذه الظاهرة على وجهة السرعة. 10. إن قيام الدولة بفرض قانون التجنيد الإلزامي مع رواتب جيدة للشباب من الممكن أن تسهم في خفض مستوى البطالة لدى الشباب. وبناء على الاستنتاجات السابقة يمكن الخروج بمجموعة من التوصيات الآتية: 1. على الدولة الاهتمام بملف العاطلين عن العمل من خلال إقامة الندوات العلمية للمتخصصين في هذا الجانب من أجل تقليل الفجوة بين عدد الخريجين وسوق العمل. 2. إنعاش القطاع الخاص من خلال توفير الأساس القانوني للاستثمار الأجنبي والمحلي. 3. تطوير مهارات الخريجين من خلال اللجوء إلى التطورات المعاصرة في مجال التعليم والتعلم. 4. تخصيص منح مالية سريعة لفئة العاطلين عن العمل من أجل تقديم العون على وجه السرعة. 5. توجيه المؤسسات الإعلامية إلى تسليط مزيد من الضوء على موضوع البطالة الإجبارية التي تعاني منها فئة الشباب. 6. توجيه المؤسسات الطوعية إلى الاهتمام بملف الشباب والبطالة التي تعاني منها هذه الفئة من خلال إقامة الدورات التدريبية التطويرية التي تطور من مهاراتهم فيما يتعلق بالعمل الخاص. The city of (Sadr) in Baghdad is considered one of the most crowded areas in terms of population, as well as the number of young graduates who are highly qualified for work, but for many political, economic and security reasons, the majority of the city's youth were not able to obtain permanent work, whether in the public or private sectors, and in Our current research will discuss the issue of compulsory unemployment suffered by the youth of this city, hoping to come up with proposals that address this phenomenon. The current research seeks to identify the phenomenon of compulsory unemployment among a sample of unemployed youth in the city of Baghdad (Sadr City). In light of a group of demographic variables, and in order to collect the necessary data and information, the study conducted a questionnaire to measure the research variable and extracted for it a set of appropriate statistical characteristics of validity and reliability. The tool was applied to the sample, and the study reached the following results: 1. The accumulation of graduates, whether at the level of public or private colleges, contributed to the surplus of graduates reaching a higher level than the labor market needs for them, which imposed compulsory unemployment on the youth group. 2. Compulsory unemployment is due to the poor planning and work of the competent authorities that plan for human resources in universities and the required labor market, which was negatively reflected on the reality of university graduates who are qualified to work. 3. The state's strategy of employing graduates without paying attention to the private sector is incorrect and has contributed to the exacerbation of the situation 4. Waiting for a graduate without seeking employment in the private sector or even at the level of small projects has contributed to the exacerbation of this crisis among young people. 5. The demand of students for certain majors in order to obtain a job in the future contributed negatively to raising unemployment rates 6. The state's resort to traditional education, without the presence of recent developments in methods, curricula, and teaching methods, has led to educational outputs that do not possess realistic work skills, and thus negatively reflects on the possibility of employing them at work. 7. Political corruption after 2003 contributed negatively to affecting the state's ability to absorb youth and graduates in the state's joints or in the private sector. 8. Private university education after 2003 has a negative impact on raising the size of the phenomenon of compulsory unemployment through the nature of the outputs and the number of graduates. 9. That the planning authorities in the country link the number of graduates who are really required for the labor market is important in eliminating this phenomenon as a matter of urgency. 10. The state's imposition of the compulsory conscription law with good salaries for young people could contribute to reducing the level of unemployment among young people. Based on the previous conclusions, the following set of recommendations can be made: 1. The state should pay attention to the file of the unemployed by holding scientific seminars for specialists in this aspect in order to reduce the gap between the number of graduates and the labor market. 2. Revitalizing the private sector by providing the legal basis for foreign and domestic investment 3. Developing graduates' skills by resorting to contemporary developments in the field of teaching and learning. 4. Allocating quick financial grants to the category of the unemployed in order to provide assistance quickly. 5. Directing media organizations to shed more light on the issue of compulsory unemployment that young people suffer from 6. Directing voluntary institutions to pay attention to the issue of youth and unemployment that this group suffers from, by holding developmental training courses that develop their skills in relation to private work.
Keywords: الجغرافيا السكانية -- ظاهرة البطالة -- خريجي الجامعات -- بغداد